Aspiration Biopsy Cytology of Non Neoplastic Lymphadenopathies Accompanied by Necrosis - Dipti Anu; Soumya B.M.; Rashmi P.; Thumma Deepika Poornima; SS Hiremath (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Necrosis in lymph node biopsy is relatively common observation. It may be seen in wide range of neoplastic and non-neoplastic lesions. However, the pattern and extent of necrosis are often distinctive for certain entities, or at least may suggest a limited number of possibilities in the differential diagnosis. This emphasizes the need for assessing the diagnostic utility of aspiration biopsy cytology of non neoplastic lymphadenopathies accompanied by necrosis. Objectives: 1) To study the cytological features in non neoplastic lymph node aspiration accompanied by necrosis. 2) To correlate with histopathology wherever possible. Material: A total of 193 patients with lymphadenopathy were included in the study. This is a prospective study, undertaken in the Department of Pathology, J.J.M. Medical College, Davangere, during the period of July 2014 to June 2016. Result: Our study included 193 patients with lymphadenopathy accompanied by necrosis. Age group ranged from four months to 82 years. Among the 193 patients, most common non neoplastic lesions with necrosis encountered were tubercular lymphadenitis in 134 cases and acute suppurative lymphadenitis in 52 cases. Conclusion: Fine needle aspiration cytology of the lesions in lymph node was proved to be useful technique for the evaluation of patients having lymphadenopathies with necrosis. The pattern and extent of necrosis suggests a limited number of possibilities in differential diagnosis.